Proceedings of the International Academic Conference on Education 2019
DOI: 10.33422/iaceducation.2019.11.666
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Health and Safety in Science Laboratories in Saudi Arabian Secondary Schools

Abstract: This paper presents the findings of a study that investigated teachers' perceptions of health and safety risks in science laboratories in secondary schools in Saudi Arabia. It identified the level of knowledge of school staff about health and safety risks and reviewed the current practices in the schools. A mixed methods study design was utilised to investigate the phenomenon. A stratified random sampling technique was used to select male and female teachers from 19 secondary schools in two cities, Jeddah and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The results indicated that Arabic texts emphasize using more compound phrases than texts written in English. Alshehri (2023) found that translators play a key role in the tourism industry in the Kingdom of Saudi Arabia because they act as cross-cultural communicators and cultural bridge builders by transferring the knowledge of the native culture and national heritage to tourists while also strengthening the image of Saudi Arabia before international visitors and tourists.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The results indicated that Arabic texts emphasize using more compound phrases than texts written in English. Alshehri (2023) found that translators play a key role in the tourism industry in the Kingdom of Saudi Arabia because they act as cross-cultural communicators and cultural bridge builders by transferring the knowledge of the native culture and national heritage to tourists while also strengthening the image of Saudi Arabia before international visitors and tourists.…”
Section: Previous Studiesmentioning
confidence: 99%